The Notion of Hyper-wandering in Apprehending the Mobility of Israelis After the Army Along the Andes Cordillera - Arnaud Szkutnicki; Pascal Mao (Revue de Géographie Alpine)
Through the study of Israeli tourist mobility, this article questions the interrelations between wandering and hypermobility. In Israel, travelling after the completion of compulsory military service is a valued practice in contemporary society, and several thousand recently discharged young people pursue this faraway wandering every year. This article examines the phenomenon of post-military travel in Chile by proposing an approach based on spatial and virtual mobility and on the motility capital of the practitioners. The analysis of these mobilities reveals a form of long, flexible and virtually connected wandering that is part of the era of hypermobility. The insertion of the practice in a global and digitised context leads us to position it in a new category that we call hyper-wandering.